Sediment transport modeling and flood risk mapping in Geographic Information System (GIS) - Sinnakaudan, Shanker Kumar; Ghani, Aminuddin Ab.; Ahamad, Mohd. Sanusi F.; Zakaria, Nor Azazi (Penerbit Universiti Sains Malaysia, 2004)
Most computer models used in the flood risk analysis of rivers have inadequate functions in its spatial analytical capabilities and without sediment transport simulation capacity or suitable equations to represents correctly in-situ hydraulic processes (Sinnakaudan et al., 2001, Sinnakaudan, 2003). Further more, the consistent deficiencies of these models are their inability to connect the information describing the water profiles with their physical locations on the land surface. This is where a Geographic Information System (GIS) becomes a valuable tool in spatial modeling for engineers, planners and geoscientist (Burrough, 1998; Sinnakaudan et.al, 2003).